E-cognocracy and the participation of immigrants in e-governance - José María Moreno-Jiménez; Wolfgang Polasek (Institute for Advanced Studies (IHS), 2005)
This paper develops a new approach for a political support system related to the integration of immigrants using e-governance. Through the Internet the participation of immigrants is possible in both societies, the original and the new one, and at the three different levels: local, regional and national. Using the Analytic Hierarchy Process (AHP), we discuss how to consider immigrants as e-citizens and, through a questionnaire, and we measure the relative importance of these attributes for party decision makers. The focus of this paper is less on technological aspects of e-decision making, or the diffusion of knowledge and e-learning; Rather on the new aspects as how to integrate immigrants in e-governance. The mission is to increase the society-oriented knowledge derived from participatory decision-making and to increase the background and the scope of the learning process that goes along with the modification of the initial preferences in the interactive political resolution process.
Keywords: H10; 330; e-cognocracy; e-democracy; e-citizen; e-participation; immigration; knowledge society; Einwanderung; Soziale Integration; Öffentliche Verwaltung; Internet